Transformations of the Inner Self in Ancient Religions - Assmann, Jan.; Stroumsa, Guy G. (Numen Book Series, 1999)
This collection of papers from two workshops - held in Heidelberg, Germany, in July 1996 and Jerusalem, Israel, in October 1997 - is concerned with anthropological rather than theological aspects of the Near Eastern and Mediterranean religions, ranging from the 'primary' religions of the archaic period and their complex developments in Egypt and Mesopotamia to the 'soteriological' movements and 'secondary' religions that emerged in Late Antiquity. The first part of the book focuses on \'Confession and Conversion\', while the second part is devoted to the topic of \'Guilt, Sin and Rituals of Purification\'. The primary purpose of this volume is to convey a sense of the dynamics and dialectical relationships between the various Near Eastern and Mediterranean religions from the archaic period to Late Antiquity.